Pengaruh Model Learning Cycle 5E Terhadap Hasil Belajar IPA Pada Materi Bunyi Dan Sifatnya di Kelas V Sekolah Dasar - Sari, Nurmala; Rahmi, Laili (Jayapangus Press, 2024)
The problem that is often encountered during the teaching and learning process in the classroom is that learning still refers to the teacher as the information provider, by only relying on textual books as learning references. Thus, students only have limited opportunities to read material and listen to teacher explanations. So to overcome this, a 5E learning cycle model is needed. This research aims to determine the effect of implementing the Learning Cycle 5E learning model on the learning outcomes of class V students in science subjects at SD Negeri 48 Pekanbaru. This research uses a quantitative approach with an experimental type. This research used a one-group pretest posttest design. The population in this research involved all class V students at SDN 48 Pekanbaru. The sample for this research consisted of 40 students from class VA at SDN 48 Pekanbaru. The data collection technique in this research uses tests with research instruments in the form of pretest and posttest test questions. The hypothesis technique in this research uses the Two Related Mean Difference Test method (Paired sample t-test). Based on the research findings, it can be concluded that there is an influence of the application of the 5E cycle learning model on the learning outcomes of sound and nature science material in class V at SDN 48 Pekanbaru.